Theater Performing Art: a Strategy to Improve Self-efficacy and Social Support in Patient with Type 2 diabetes Mellitus (T2DM) - Mahendro Prasetyo Kusumo (Journal of Global Pharma Technology, 2020)
Background: The lacks of self-efficacy and social support are two neglected issues in patients with type 2 diabetes mellitus (T2DM). One of the popular methods to enhance those factors is theater performance art education (TPA), but its evidence in T2DM is lacking. Therefore, this study was aimed to measure the effectiveness of TPA toward social support and self-efficacy in T2DM. Methods: This study used quantitative methods with a quasi-experimental non-equivalent pre post-test control group design. The two variables measured were self-efficacy and social support. The subjects of this study were Prolanist member of patients with T2DM in the four primary health care centers in Sleman Yogyakarta Indonesia. Pre-test and post-test measurement were taken and compared to determine the efficacy of the TPA. Results: 102 subjects were used in this study (32 in control and 70 in intervention group) with women and 45-60 years old age group comprised the majority of the subject population. Mann-Whitney test showed that the self-efficacy score increased more pronouncedly in intervention group compared to control group (Δ mean intervention: 3.34±4.74; Δ mean control: -0.75±3.98; p: 0.000). Same result was also observed in social-support variable (Δ mean intervention: 1.63±1.84; Δ Mean control: 0.38±1.84; p: 0.002). Multiple logistic regression revealed that TPA only significantly affected self-sufficiency (Adjusted OR: 0.173; p: 0.001; 95%CI: 0.062 - 0.479) while barely influenced social support. Conclusion: The implementation of theater performing art-based community empowerment as part of social education helps in improving self-efficacy in patients with T2DM. Keywords: T2DM, Theater performing art, Self-efficacy, Social support.